Colombia : First Review Under the Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper examines the First Review Under the Stand-By Arrangement for Colombia. Under the authorities' program, economic performance has been mostly favorable. Real economic growth appears to be recovering, led by a pickup in domestic demand that outweighed a decline in net exports. Inflation, however, has remained above the program target. Since late February, the currency has appreciated, responding partly to a sharp decline in the country risk premium. The program is on track and the authorities have reiterated their full commitment to achieving the main elements of the program's macroeconomic framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet